Synthesis, Characterisation and DFT Calculations of Azo-Imine Dyes - Özkinali, Sevil; Çavuş, Muhammet Serdar; Umur Saki̇n, Büşra (The Turkish Chemical Society, 2017)
In this study, azo dyes containing an imine group were synthesised by coupling p - hydroxybenzylidene aniline with the diazonium salts of p -toluidine, 4-aminophenol, aniline, p -chloroaniline, p - fluoroaniline and p -nitroaniline. The compounds were characterised by melting point, elemental, UV - Vis and IR analyses as well as 1 H-NMR and 13 C-NMR spectroscopies. Moreover, the experimental data were supplemented with density functional theory (DFT) calculations. The experimental data on FT-IR and UV–Vis spectra of the compounds were compared with theoretical results. The DFT calculations were performed to obtain the ground state geometries of the compounds using the B3LYP hybrid functional level with 6-311++g(2d,2p) basis set. Frontier molecular orbital energies, band gap energies and some chemical reactivity parameters , such as c hemical hardness and electronegativity , were calculated and compared with experimental values . A significant correlation was observed between the dipole moment and polarities of the solvents and the absorption wavelength of the compounds.
Keywords: Engineering; Azo-Imine; Azo-imine; Schiff Bases; DFT; Mühendislik; Azo-Azomethine; Chemical Engineering; Kimya Mühendisliği; DFT; Schiff Bases; Spectroscopy